2016
DOI: 10.1037/ser0000079
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a self-administered intervention for criminal thinking: Taking a Chance on Change.

Abstract: The current study tested the effectiveness of a self-administered, cognitive-behavioral intervention targeting criminal thinking for inmates in segregated housing: Taking a Chance on Change (TCC). Participants included 273 inmates in segregated housing at state correctional institutions. Reductions in criminal thinking, as assessed by the Psychological Inventory of Criminal Styles-Simplified Version, were found in the general criminal thinking score as well as the proactive and reactive composite scores. Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
0
21
0
2
Order By: Relevance
“…Proactive criminal thinking, like most forms of irrational cognition, lends itself to cognitive behavioral intervention, which research indicates is particularly effective in reducing offending in both juveniles and adults (Landenberger & Lipsey, 2005; Lipsey et al, 2001; Pearson et al, 2002; Wilson et al, 2005). In fact, several studies have specifically found that proactive criminal thinking responds to cognitive behavioral intervention (Folk et al, 2016; Warner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Proactive criminal thinking, like most forms of irrational cognition, lends itself to cognitive behavioral intervention, which research indicates is particularly effective in reducing offending in both juveniles and adults (Landenberger & Lipsey, 2005; Lipsey et al, 2001; Pearson et al, 2002; Wilson et al, 2005). In fact, several studies have specifically found that proactive criminal thinking responds to cognitive behavioral intervention (Folk et al, 2016; Warner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, important and useful internal trends that contribute to convicts' rehabilitation, improvement of the effectiveness of educational, psychological and other activities in a correctional institution, on the contrary, fade away. The processes of rethinking one's actions, lifestyle, and social ties that led a person to commit a crime are replaced by increasing negative emotions and anger; criminal experience and criminal infection are formed [17]. Forced long-term coexistence with other convicts that differ in their social, moral, psychological, intellectual qualities, as well as the state of health, including mental health, leads to the development of negative features in the personality of convicts.…”
Section: Resultsmentioning
confidence: 99%
“…A more realistic alternative would be to engage inmates in cognitive-behavior therapy as a way of enhancing their internal coping skills through stress and anger management and positive self-talk (Tafrate & Mitchell, 2014). Two programs developed specifically for inmates in restrictive housing, Taking a Chance on Change (Folk et al, 2016) and Stepping Up and Stepping Out (Batastini et al, 2021), have produced promising initial results using a cognitive-behavioral framework. The symptoms of SHU syndrome can also be managed by avoiding single-person cells in restrictive housing, as long as this does not put an inmate in jeopardy.…”
Section: Practical Implicationsmentioning
confidence: 99%